Outcome and predictors for smoking cessation in a Quit Smoking Clinic - Zainal Abidin, Muhammad 'Adil; Kadir@Shahar, Hayati; Abdul Manaf, Rosliza (2017)
Smoking is the leading preventable cause of non-communicable disease mortality worldwide. Therefore, effort for the effective measure in smoking cessation is important. However, the central problem in the nicotine addiction treatment is relapse. A retrospective cohort study was done at Tanglin Quit Smoking Clinic to determine the outcome of smoking cessation and its predictors. A cohort of 770 smokers between 2008 and 2015 were identified through simple random sampling. Smokers were defined as current smoker, while smoking abstinence is defined as cessation more than 6 months and relapse as any smoking episode even a puff since the quit date. Majority were Malays, Muslims and had secondary or higher education. The mean initiating age for smoking was 17.6 years old, with majority smoke between 11 to 20 sticks, and had high nicotine dependence score (43%). At the end of the study 52.5% of them abstinence from smoking. The predictors for smoking cessation were number of quit attempt (1 to 10 times) (AOR = 1.582, 95% CI = 1.012-2.472) and pharmacotherapy (AOR = 0.711, 95% CI=0.511-0.989). More frequent follow up was required during the first crucial 6 months to prevent relapse. Number of follow up can enhance not only the medication compliance but also motivational aspect to smokers to reduce relapse rates. Healthcare provider should give extra attention to the potential relapser especially to those who attempt for the first time.